Outcomes of Cochlear Implantation in Patients with Post-Meningitis Deafness: A Systematic Review and Narrative Synthesis - Singhal, Kaajal (J Int Adv Otol, 2020)
Summarise outcomes following cochlear implantation (CI) in patients with post-meningitis deafness. Systematic review and narrative synthesis. Databases searched: Medline, Pubmed, Embase, Web of Science, Cochrane Collection and ClinicalTrials.gov. No limits placed on language or year of publication. Studies with a minimum of 20 individuals with post-meningitis deafness were included. Review conducted in accordance with the PRISMA statement. Searches identified 906 abstracts and 291 full texts. Of these, 19 studies met the inclusion criteria, reporting outcomes in 610 patients with 650 implants. Audiological outcomes improved across all studies following cochlear implantation. 7 studies demonstrated a statistically significant difference between pre and post-CI outcomes. Patients with no cochlear ossification, full electrode insertion, shorter duration of deafness and no neurological sequelae generally appeared to perform best. A total of 31 minor and 19 major complications were reported, with 15 cases of reimplantation. The methodological quality of the included studies was sufficient, predominantly consisting of cohort studies. 15 studies were OCEBM grade III and 4 studies were OCEBM grade IV. All studies had a minimum of 20 individuals with post-meningitic deafness and used multi-channel cochlear implant devices. Audiological outcomes following cochlear implantation in meningitis are satisfactory, providing functional levels of speech perception and intelligibility. Improvement in hearing is dependent on the amount of cochlear ossification, duration of deafness prior to implantation, electrode insertion depth and presence of neurological sequalae. Cochlear implantation in meningitis patients can be challenging due to the presence of ossification and inaccuracies of pre-operative imaging. Therefore, early and bilateral implantation is recommended in all patients with post-meningitis hearing loss to improve the likelihood of full electrode insertion.